ChemInform Abstract: Li Intercalation into 1D TiS2(en) Chains. Issue 25 (24th June 2014) - Li, Tianyang; Liu, Yi‐Hsin; Chitara, Basant; Goldberger, Joshua E.
Abstract Hybrid organic/inorganic van der Waals solid TiS2(en) is prepared by solvothermal reaction of a sulfur solution in en mixed with a TiCl4 solution in PhCl (Teflon cup in evacuated Parr reactor, 200—220 °C, 5 d) followed by purification via repeated recrystallization of the gel‐like product and centrifugation.